Virtual simulation and home-based manipulatives: Improving the practice of physics teaching - Bonifacio, Anna Carmela B. (Animo Repository, 2022)
Schools fast-tracked and implemented abridged curricula in response to the cessation of classes brought about by the pandemic. Foreshortened curricula featured the essential learning competencies and various alternatives to the traditional form of teaching. The objectives were to provide continuity in learning and preserve students’ motivation despite the school lockdowns. The study-at-home setup went full swing with an abbreviated and technologized curriculum for SY 2020-2021 and remained in effect for a second school year, SY 2021-2022. Commendably were the efforts of public school officials and local government units to provide gadgets and data load for those in need. In place of hands-on classroom experiments, science teachers are to use virtual experiment simulations, which students themselves will execute at home. Virtual simulations had been in some limited use by teachers who opted for them, but this time, simulations are to serve as the default for science teachers. Inquiry, actual experiments, and manipulation of devices are inherent components of learning and student motivation in the practice of teaching science. Although virtual simulations were the official school prescriptions, the possibility of do-it-at-home experiments for students was explored. The study aimed to research how both virtual and actual experiments performed by students at home might bring about gains in student motivation. A critical task of teachers is to support students’ autonomy through relevant opportunities that increase motivation to learn. Therefore, a group of students were provided with virtually simulated experiments and another group with a set of manipulative science learning tools, referred to as Home Based Manipulatives, to perform experiments independently, guided by the accompanying modules. This study was undertaken to provide a research-based evaluation of the Simulations and the Home Based Manipulatives in view of contributing to the practice of Physics teaching. The researcher analyzed the motivation and academic performance in the group of students who experienced Physics experiments using computer simulations and in the group of students who did actual experiments using Home-Based Manipulatives. Results show that in both groups, there was a gain in motivation and academic performance. Furthermore, both Simulation and HBM students expressed positive feedback regarding the experiment mode they had experienced. The statistics and the student reflections revealed that each strategy is inherently connected to specific desired learning competencies, results which can serve as strategies for teaching practice. Keywords: Experiential Learning, Abridged Curriculum, Motivation, Simulations, Homebased Manipulatives